Comparative genome analysis of Salmonella Enteritidis PT4 and Salmonella Gallinarum 287/91 provides insights into evolutionary and host adaptation pathways - Thomson, Nicholas R.; Clayton, Debra J.; Windhorst, Daniel; Vernikos, Georgios; Davidson, Susanne; Churcher, Carol; Quail, Michael A.; Stevens, Mark; Jones, Michael A.; Watson, Michael; Barron, Andy; Layton, Abigail; et al. (Genome Research, 2008)
We have determined the complete genome sequences of a host-promiscuous Salmonella enterica serovar Enteritidis PT4 isolate P125109 and a chicken-restricted Salmonella enterica serovar Gallinarum isolate 287/91. Genome comparisons between these and other Salmonella isolates indicate that S. Gallinarum 287/91 is a recently evolved descendent of S. Enteritidis. Significantly, the genome of S. Gallinarum has undergone extensive degradation through deletion and pseudogene formation. Comparison of the pseudogenes in S. Gallinarum with those identified previously in other host-adapted bacteria reveals the loss of many common functional traits and provides insights into possible mechanisms of host and tissue adaptation. We propose that experimental analysis in chickens and mice of S. Enteritidis–harboring mutations in functional homologs of the pseudogenes present in S. Gallinarum could provide an experimentally tractable route toward unraveling the genetic basis of host adaptation in S. enterica.